2011
DOI: 10.1128/mcb.05231-11
|View full text |Cite
|
Sign up to set email alerts
|

The Tightly Controlled Deubiquitination Activity of the Human SAGA Complex Differentially Modifies Distinct Gene Regulatory Elements

Abstract: The multisubunit SAGA coactivator complex facilitates access of general transcription factors to DNA through histone acetylation mediated by GCN5. USP22 (ubiquitin-specific protease 22) was recently described as a subunit of the human SAGA complex that removes ubiquitin from monoubiquitinated histone H2B and H2A in vitro. Here we demonstrate an allosteric regulation of USP22 through multiple interactions with different domains of other subunits of the SAGA deubiquitination module (ATXN7, ATXN7L3, and ENY2). Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(159 citation statements)
references
References 38 publications
9
150
0
Order By: Relevance
“…The latter study provided data suggesting that SAGA DUB interacts with chromatin in a Pol II transcription‐independent manner. Studies in different eukaryotes have suggested that the presence of SAGA at the promoters of genes is needed to facilitate Pol II recruitment and pre‐initiation complex (PIC) formation (Wyce et al , 2007; Nagy et al , 2009; Helmlinger et al , 2011; Lang et al , 2011). The recruitment of SAGA and ATAC coactivator complexes to genomic loci has been suggested to take place by several distinct mechanisms: (i) by activator mediated recruitment (McMahon et al , 1998; Brown et al , 2001; Fishburn et al , 2005; Reeves & Hahn, 2005), (ii) by interactions with basal transcription machinery components (Larschan & Winston, 2001; Laprade et al , 2007; Mohibullah & Hahn, 2008) and (iii) through chromatin‐interacting domains of SAGA and ATAC subunits (Hassan et al , 2002; Vermeulen et al , 2010; Bian et al , 2011; Bonnet et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The latter study provided data suggesting that SAGA DUB interacts with chromatin in a Pol II transcription‐independent manner. Studies in different eukaryotes have suggested that the presence of SAGA at the promoters of genes is needed to facilitate Pol II recruitment and pre‐initiation complex (PIC) formation (Wyce et al , 2007; Nagy et al , 2009; Helmlinger et al , 2011; Lang et al , 2011). The recruitment of SAGA and ATAC coactivator complexes to genomic loci has been suggested to take place by several distinct mechanisms: (i) by activator mediated recruitment (McMahon et al , 1998; Brown et al , 2001; Fishburn et al , 2005; Reeves & Hahn, 2005), (ii) by interactions with basal transcription machinery components (Larschan & Winston, 2001; Laprade et al , 2007; Mohibullah & Hahn, 2008) and (iii) through chromatin‐interacting domains of SAGA and ATAC subunits (Hassan et al , 2002; Vermeulen et al , 2010; Bian et al , 2011; Bonnet et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several DUBs require assembly into large multimolecular complexes for full activation, exemplified by the proteasomal DUBs which are discussed in detail below. Another example is provided by the allosteric activation of USP22 by multiple components of the SAGA coactivator complex (118,138,223). Simpler instances of allosteric regulation are found with the increase in k cat following interaction of USP1, USP12, and USP46 with UAF1 (WDR48) (40, 41).…”
Section: Regulation Of Dub Activitymentioning
confidence: 99%
“…GCN5 and PCAF, which were also recruited and shown to acetylate H3K9, were dispensable for transcription initiation in this system [35], but may play a role in maintaining expression [93]. In addition, GCN5 and PCAF are components of multiprotein Studied in cell lines [46]; not yet investigated in visual systems complexes with additional functions [46,94], and so their presence may indicate recruitment of other regulatory activities.…”
Section: Histone Acetylation In Retinal Ganglion Cellsmentioning
confidence: 99%
“…The disease protein ataxin-7 (ATXN7) is a component of a large chromatin remodeling complex that is highly conserved from yeast (SAGA) to man (STAGA/TFTC). Among a number of general transcription factors/cofactors, the STAGA complex contains two key chromatin remodeling factors: GCN5 HAT for acetylation of histone H3 (Table 3); and USP22 (ubiquitin-specific protease 22) that removes ubiquitin from monoubiquitinated histone H2B and H2A (Table 5), required for full activation of STAGAdependent inducible genes [46,114,115]. Using transgenic and knockin mouse models with retinal degeneration beginning at 4 weeks of age, it was found that assembly of the STAGA complex is impaired, reducing GCN5 activity on photoreceptor gene promoters, [91] and severely decreasing photoreceptor gene transcription [116].…”
Section: Histone Modifications In Photoreceptor Gene Expressionmentioning
confidence: 99%